Effect of water immersion, laundering, and abrasion on the conductivity of reduced graphene oxide coatings on aramid fabrics. Issue 1 (April 2020) - Cho, Chungyeon; Elias, Anastasia L; Batcheller, Jane; Chung, Hyun-Joong; Dolez, Patricia I
Abstract: Opportunities for developing end-of-life sensors for fire resistant fabrics are explored using reduced graphene oxide coatings on textiles. Fire resistant fabrics are known to experience significant losses in performance over time. Large reductions in mechanical properties have also been recorded when these fabrics were subjected to accelerated aging conditions simulating the use in service. In addition, the fabric loss in performance may exceed the safety requirement threshold before any sign of damage is visible to the naked eye. Electrically conductive coatings and tracks were prepared on an m-aramid woven fabric using graphene oxide that was further reduced. The preparation technique allowed wrapping the individual aramid fibers with rGO sheets. No significant change in sheet resistance was recorded after up to 120h of immersion of the rGO-coated fabric specimens in water. An increase in resistance after 10 accelerated washing cycles was measured on the rGO-coated specimens prepared with 5 coating cycles while no significant effect was detected for specimens prepared with 10 and 15 coating cycles. Under abrasion exposure, the electrical resistance of rGO tracks increased gradually until 150 cycles, after which the conductivity dropped abruptly. These results show the potential of reduced graphene oxide applied as a coating on m-aramid fabrics to prepare end-of-life sensors for fire resistant fabrics.